2015
DOI: 10.1016/j.burns.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Preventing childhood scalds within the home: Overview of systematic reviews and a systematic review of primary studies

Abstract: HighlightsWe performed an overview of published systematic reviews and a systematic review of primary studies evaluating the effectiveness of interventions to prevent scalds in childhood.There is little evidence that interventions are effective in reducing the incidence of scalds in children.There is no consistent evidence on the effectiveness of interventions on the safe handling of hot food or drinks nor improving kitchen safety practices.Education, home safety checks along with thermometers or thermostatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 55 publications
(131 reference statements)
0
20
0
7
Order By: Relevance
“…19 Prevention in developing countries is absolutely different from that of developed countries, where burn prevention has been integrated to their education and community systems. 12 However, it should be the goal of the developing countries for conducting continuous education on burn prevention as good knowledge will lead to good practice that will significantly reduce burnrelated disfigurement, disability, and death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Prevention in developing countries is absolutely different from that of developed countries, where burn prevention has been integrated to their education and community systems. 12 However, it should be the goal of the developing countries for conducting continuous education on burn prevention as good knowledge will lead to good practice that will significantly reduce burnrelated disfigurement, disability, and death.…”
Section: Discussionmentioning
confidence: 99%
“…10 Similar results of improvements can be seen in other health promotion programs. 11,12 Health promotion is considered an important tool to counter socioeconomic problems and should be supported by simple, cost-effective, innovative, and culturally and geographically appropriate models. 13,14 Burn injuries should be considered preventable and public health approaches that provide interdisciplinary education and prevention programs can help to prevent them.…”
Section: Introductionmentioning
confidence: 99%
“…Der Altersgipfel liegt bei 0 bis 4 Jahren; diese Patientengruppe macht mit 50 bis 70 % den größten Teil aller Vorstellungen in Einrichtungen der Akutversorgung aus [9,17,18,29]. Kleinkinder entdecken mit steigenden motorischen Fähigkeiten ihre Umgebung, sind jedoch nicht in der Lage, mögliche Gefahren zu erkennen und benötigen ständige Beaufsichtigung [17,24,34]. Jungen sind häufiger betroffen als Mädchen [29].…”
Section: Introductionunclassified
“…Several studies have suggested passive prevention approaches to HBS through cup design [55,89]; such as widebased slip-proof cups, lidded cups to reduce the amount of spill (like travel mugs), or cups that visually warn people of high temperatured content inside. [90][91][92] However, there are no studies in the literature that evaluate the efficacy of these designs. As noted above, passive approaches often require effort on the part of the individual, so to be successful, people need to have awareness and feel compelled to use these cup designs, which may be not be practical or acceptable.…”
Section: Injury Prevention and Behaviour Change Theorymentioning
confidence: 99%
“…Of the scald interventions that have been undertaken, few have been evaluated as effective. [45,85,92] However, this may be due to lack of adequate evaluation. [105] (shown in Figure 8), even though the ultimate outcome measure is to reduce the number of injuries (or death), this may take a long time to achieve.…”
Section: Injury Prevention and Behaviour Change Theorymentioning
confidence: 99%